PENGARUH METODE PEMBELAJARAN BERBASIS PROYEK TERHADAP KREATIVITAS SISWA PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 040454 PECEREN - Wenny Novi Yanti Sipakkar; Wisno Saputra Sembiring; Nurlia Ginting (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing project-based learning (PJBL) on the creativity of fourth-grade students at SD Negeri 040454 Peceren. This study used quantitative approach and a one- group pretest-posttest design, meaning teh study was conducted one group without a control group. The study subjects were 31. Data collection techniques used in this study included questionnaires, observation, and documentation. Prior to use, the instrument was tested for validity and reliability. The results of the realibility tets cronbach`s alpha value of 0,709, indicating that the instrument was reliable. Data analysis showed that the average pretest score was 49,8710 and the posttest score was 78,9032. The shapiro-wilk test for normality indicated that the data were not normally distributed, so the hypothesis was tested using the Wilcoxon Single-Single Rank Test. The Wilcoxon test showed a significance value of 0.01, thus rejecting H0 and accepting Ha. Based on these results, it can be concluded that the implementation of project-based learning (PLBL) has a significant effect on the creativity of fourth-grade students at SD Negeri 040454 Peceren.